2022
DOI: 10.1002/adem.202101624
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Water‐ and Ice‐Repellent Surfaces on Additive‐Manufactured Components Using Laser‐Based Microstructuring Methods

Abstract: The ORCID identification number(s) for the author(s) of this article can be found under https://doi.org/10.1002/adem.202101624.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…To surmount this challenge, Kuisat et al combined different laser micro/nanostructuring techniques, nanosecond pulse and picosecond pulse (1064 nm, 10 ns or 10 ps, 3.2 J cm −2 or 100 W), to construct multiscale structures with feature sizes between 800 nm and 21 µm (Figure 4d). [99] The treated Ti64…”
Section: Picosecond Lasermentioning
confidence: 99%
See 2 more Smart Citations
“…To surmount this challenge, Kuisat et al combined different laser micro/nanostructuring techniques, nanosecond pulse and picosecond pulse (1064 nm, 10 ns or 10 ps, 3.2 J cm −2 or 100 W), to construct multiscale structures with feature sizes between 800 nm and 21 µm (Figure 4d). [99] The treated Ti64…”
Section: Picosecond Lasermentioning
confidence: 99%
“…combined different laser micro/nanostructuring techniques, nanosecond pulse and picosecond pulse (1064 nm, 10 ns or 10 ps, 3.2 J cm −2 or 100 W), to construct multiscale structures with feature sizes between 800 nm and 21 µm (Figure 4d). [ 99 ] The treated Ti64 and Al‐Mg‐Sc (Scalmalloy) surfaces exhibited desired patterned roughness across multiple scales for implementing water‐/ice‐repellent properties. Consequently, with the micro/nanofabrication moving forward, more complex structures with high scales will be achieved by the combination of these micro/nanofabrications or the exploration of new techniques.…”
Section: Laser Micro/nanostructuring Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The ablation process in the heat-affected zones and the generated microtextures lead to a very strong increase in surface area. As a result of the laser–matter interaction, the surface chemistry is also modified by thermal influence due to the high-energy laser radiation process at ambient air, which results in a hydrophilic surface oxide layer for metallic materials and an increase of free surface energy. In this context, Kuisat et al demonstrated that additively manufactured Ti64 equipped with line-like DLIP features can be beneficial for water-repellent and anti-icing surface properties . DLIP in conjunction with ultrashort pulses (picosecond range) enables the creation of high-precision microtextures.…”
Section: Introductionmentioning
confidence: 99%
“… 21 23 In this context, Kuisat et al demonstrated that additively manufactured Ti64 equipped with line-like DLIP features can be beneficial for water-repellent and anti-icing surface properties. 24 DLIP in conjunction with ultrashort pulses (picosecond range) enables the creation of high-precision microtextures. This is primarily due to the ablation process involved, which results in minimal heat-affected zones and strongly reduces material remelting.…”
Section: Introductionmentioning
confidence: 99%